2012
DOI: 10.1128/mcb.00860-12
|View full text |Cite
|
Sign up to set email alerts
|

The Minimal Active Human SVA Retrotransposon Requires Only the 5′-Hexamer and Alu-Like Domains

Abstract: RNA-based duplication mediated by reverse transcriptase (RT), a process termed retrotransposition, is ongoing in humans and is a source of significant inter-and perhaps intraindividual genomic variation. The long interspersed element 1 (LINE-1 or L1) ORF2 protein is the genomic source for RT activity required for mobilization of its own RNA in cis and other RNAs, such as SINE/variable-number tandem-repeat (VNTR)/Alu (SVA) elements, in trans. SVA elements are ϳ2-kb hominid-specific noncoding RNAs that have resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 88 publications
(176 reference statements)
3
41
0
2
Order By: Relevance
“…We found that the SVA-derived module containing the CT-rich, Alu -like, and VNTR regions provides the competence to retrotranspose at rates beyond that of processed pseudogene formation. Recent studies investigating the structural features of SVA elements that affect their trans -mobilization frequency (Hancks et al 2012) demonstrated that removal of the Alu- like region in the context of a full-length SVA has little to no effect, whereas removal of the CT-hexamer or the VNTR region can result in a 75% decrease in activity. This is consistent with our observation that removal of the SVA-specific fragment covering CT-rich region, Alu -like region, and VNTR module from the full-length LAVA C reporter element (pLC10/LAVA C ) reduces trans -mobilization frequency by ∼98% (fig.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the SVA-derived module containing the CT-rich, Alu -like, and VNTR regions provides the competence to retrotranspose at rates beyond that of processed pseudogene formation. Recent studies investigating the structural features of SVA elements that affect their trans -mobilization frequency (Hancks et al 2012) demonstrated that removal of the Alu- like region in the context of a full-length SVA has little to no effect, whereas removal of the CT-hexamer or the VNTR region can result in a 75% decrease in activity. This is consistent with our observation that removal of the SVA-specific fragment covering CT-rich region, Alu -like region, and VNTR module from the full-length LAVA C reporter element (pLC10/LAVA C ) reduces trans -mobilization frequency by ∼98% (fig.…”
Section: Discussionmentioning
confidence: 99%
“…, human Alu and SVA elements and mouse B1 and B2 elements) (9296) and cellular mRNAs to new genomic locations, with the latter giving rise to processed pseudogenes (97, 98) (Figure 1). As expected, each of the above elements contains structural hallmarks that are consistent with being mobilized by the LINE-1 encoded proteins (reviewed in (11)).…”
Section: Transposable Elements In Mammalian Genomesmentioning
confidence: 99%
“…A recent study to determine the nature of SVA retrotransposition revealed that no individual domain of an SVA is fundamental for this to occur, but each domain differentially affected the rate at which retrotransposition can take place [13]. To date eight SVA insertions have been associated with disease [14,15], these include for example a SVA in the 3’UTR of the fukutin gene which causes Fukyama-type congenital muscular dystrophy by decreasing mRNA production, and a SVA insertion and subsequent 14 kb deletion of the HLA-A gene locus linked with leukaemia [16,17].…”
Section: Introductionmentioning
confidence: 99%